Distinct responses of abundant and rare foraminifera to environmental variables in the Antarctic region revealed by DNA metabarcoding - Li, Qingxia; Lei, Yanli; Li, Haotian; Li, Tiegang (Frontiers in Marine Science, 2023)
The Antarctic region plays a key role in regulating the Earth's climate and contains a unique record of environmental change. Foraminifera, a group of shell-bearing protists, are widely used as paleoenvironmental proxies. However, core-based reconstructions of Antarctic paleoenvironments are often hindered by the lack of foraminiferal fossil record. Foraminiferal ancient DNA provides new avenues for understanding environmental change, but the correlation between molecular ecological features of foraminifera and environmental conditions remains poorly understood. Here, we obtained surface sediment samples from the Southern Ocean at water depths ranging from 50 to 4399 m and measured eight environmental variables. We generated a DNA metabarcoding dataset of foraminifera and presented the first assessment of relationships between foraminiferal molecular diversity and environmental variables in the Antarctic region. The results showed that the alpha diversity of whole community and abundant subcommunity was positively correlated with water depth and negatively correlated with temperature, chlorophyll a and pheophytin a, while the alpha diversity of rare subcommunity had no linear correlation with the above environmental variables. Both rare and abundant foraminiferal subcommunities exhibited distance-decay relationships, but only the beta diversity of rare subcommunity showed a significant positive correlation with water depth. This study reveals contrasting biogeographical patterns of abundant and rare foraminifera and their different correlations with Antarctic environmental variables, holding promise to provide more proxies for reconstructing past environments using foraminiferal ancient DNA and more information for predicting the impact of future environmental changes on polar biodiversity.